Astronomers Anonymous Getting Help with the Puzzles and Pitfalls of Practical Astronomy - Ringwood, Steve; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
In this entertaining parody of letters to a typical lonely hearts columnist, real-life expert and long-time astronomy columnist Steve Ringwood presents a sweeping overview of common questions and problems practical and amateur astronomers face, compiled from Ringwood's own experiences in the world of astronomy. His screamingly funny comments will keep you laughing out loud throughout, so be careful of reading this book in public! Written especially for troubled astronomers, but also accessible to anyone with an interest in space or astronomy, readers will easily recognize the difficulties they face and enjoy the humor being directed at them and their science.
Some Background -- Fundamentals -- Instrumental Hiccups -- Medical Maladies -- Guiding the Naïve -- Observational Tips -- The Expert -- Social Torments.
Keywords: Physics; Astronomy; Physics; Astronomy, Astrophysics and Cosmology; Popular Science in Astronomy